1988
DOI: 10.1364/ao.27.000155
|View full text |Cite
|
Sign up to set email alerts
|

Outer scale of turbulence appropriate to modeling refractive-index structure profiles

Abstract: The outer scale of turbulence L (0) has been calculated from values of the refractive-index structure coefficient C(2)(N) obtained from spatio-angular correlation measurements of stellar scintillation. It is found that L(0) Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
93
0
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(96 citation statements)
references
References 9 publications
1
93
0
2
Order By: Relevance
“…But as pointed out by Coulman et al (1988) Coulman et al (1986), using a model developed by André et al (1978), have shown that, even if the results were not as good as expected, the model Masciadri et al (2001) considering the temperature near the ground and around the telescope at the Roque de Los Muchachos Observatory. The simulations are close to the measurements, with a comparable dispersion, but the physical time for the model to reach a thermodynamic and kinetic equilibrium is at least 3 hr.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…But as pointed out by Coulman et al (1988) Coulman et al (1986), using a model developed by André et al (1978), have shown that, even if the results were not as good as expected, the model Masciadri et al (2001) considering the temperature near the ground and around the telescope at the Roque de Los Muchachos Observatory. The simulations are close to the measurements, with a comparable dispersion, but the physical time for the model to reach a thermodynamic and kinetic equilibrium is at least 3 hr.…”
Section: Introductionmentioning
confidence: 93%
“…Models derived from the Tatarski formula give profiles 2 C N from meteorological data. According to Coulman et al (1988), it should be possible to deduce the profile from the ). The temperature T in K, the pressure P in hPa, and the mean potential temperature 2 v in K are function of the altitude h in m. Tatarski's formula is derived from the study of the microstructure of the concentration of conservative and passive additives in a turbulent flow.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that the use of a single L 0 is not adequate to describe the spatial coherence of the atmosphere, since the response function can be the result of combining slopes from more than one layer, each with different outer scale values, i.e. a profile or L 0 (h) (Coulman et al 1988;Lukin, Fortes & Nosov 1998;Dali et al 2010;Ziad et al 2013). …”
Section: Estimating the Integrated Lmentioning
confidence: 99%
“…These models are empirical and up to now nothing could decide in favour of one of them. In addition, the small values found for the outer scale (Coulman et al 1988) reduce significantly the inertial range and therefore the Kolmogorov model field to take into account the turbulence effects in the performance of large telescopes and long baseline interferometers.…”
Section: Introductionmentioning
confidence: 99%